Identifikasi Kompetensi yang Dibutuhkan Sebagai Ahli Muda Manajemen Konstruksi - Ananda Heru Pratama; Lenggogeni Lenggogeni; R. Eka Murtinugraha (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Carrying out construction activities is a complicated activity, problems often occur in the implementation of construction projects causing the owner to experience losses, obstacles that are often faced include delays in project completion time, project cost overruns and inconsistencies in the quality and quality of construction projects. As a solution, competent experts are needed who can manage and control construction projects to avoid the obstacles that often occur. Young Construction Management Experts are one of the experts regulated in SKKNI No. 390 of 2015 to manage and control all activities starting from the planning, design, tendering, implementation, to the post-implementation stages of construction projects. This article aims to identify the competencies needed to become a Young Construction Management Expert using the literature study method. The results obtained were 30 competencies of Young Construction Management Experts which were grouped into 3 aspects, namely knowledge aspects, skills aspects and attitude aspects. These 30 competencies were obtained from SKKNI and relevant journals and books.